Dinamika Tinggi Muka Air Tanah Pada Lahan Gambut Yang Terbakar - Nur Wakhid; Siti Nurzakiah; Zainudin Zainudin (Universitas Lambung Mangkurat, 2019)
Seasonal fluctuations of water table depth are very important regarding the sustainable peat management on tropical peatland. Water level depth can affect the greenhouse gases emissions and as the main indicator for peat fire risk management. Therefore, direct measurement of water level dynamics in the peat burning area is absolutely necessary. The research objective was studied the water level fluctuations on burning peatland in Central Kalimantan, Indonesia. Water level measurement performed manually in the field and ditch, every week from February to December 2014. Water level from February to December 2014 were -86.6 and -51.9 cm, on the ditch and field, respectively. Peat soil water level was strongly correlated to the variations of rainfall.